IDO1 and inflammatory neovascularization: bringing new blood to tumor-promoting inflammation - Muller, Alexander J.; Mondal, Arpita; Dey, Souvik; Prendergast, George C. (Frontiers in Oncology, 2023)
In parallel with the genetic and epigenetic changes that accumulate in tumor cells, chronic tumor-promoting inflammation establishes a local microenvironment that fosters the development of malignancy. While knowledge of the specific factors that distinguish tumor-promoting from non-tumor-promoting inflammation remains inchoate, nevertheless, as highlighted in this series on the ‘Hallmarks of Cancer’, it is clear that tumor-promoting inflammation is essential to neoplasia and metastatic progression making identification of specific factors critical. Studies of immunometabolism and inflamometabolism have revealed a role for the tryptophan catabolizing enzyme IDO1 as a core element in tumor-promoting inflammation. At one level, IDO1 expression promotes immune tolerance to tumor antigens, thereby helping tumors evade adaptive immune control. Additionally, recent findings indicate that IDO1 also promotes tumor neovascularization by subverting local innate immunity. This newly recognized function for IDO1 is mediated by a unique myeloid cell population termed IDVCs (IDO1-dependent vascularizing cells). Initially identified in metastatic lesions, IDVCs may exert broader effects on pathologic neovascularization in various disease settings. Mechanistically, induction of IDO1 expression in IDVCs by the inflammatory cytokine IFNγ blocks the antagonistic effect of IFNγ on neovascularization by stimulating the expression of IL6, a powerful pro-angiogenic cytokine. By contributing to vascular access, this newly ascribed function for IDO1 aligns with its involvement in other cancer hallmark functionalities, (tumor-promoting inflammation, immune escape, altered cellular metabolism, metastasis), which may stem from an underlying role in normal physiological functions such as wound healing and pregnancy. Understanding the nuances of how IDO1 involvement in these cancer hallmark functionalities varies between different tumor settings will be crucial to the future development of successful IDO1-directed therapies.